Dental Profiling and Findings of Multiple Jaw Fractures in Traffic Accident Victims: A Case Report - Yunus, Aditia Dedek; Ferry P. , Gultom; Ria , Puspitawati; Fitri Ambar , Sari; Eko , Prastyo; Ferdy , Rijaldi; Suripto (Fakultas Kedokteran Gigi Unjani, 2024)
Motorcycle riders have a high rate of death and severe injury. Traffic accidents can cause blunt trauma. In this case report, authors present cases of accidents with findings of facial trauma to the forehead, nose, cheeks, and multiple fractures of the maxilla and mandible due to a hard object impact. High-speed crashes are common in polytraumatized motorcycle crashes and often display facial injuries. If regarded from the biomechanics of trauma, there is a suspicion that the victim was wearing a helmet, with direct face trauma shown by minimal abrasions on the victim's face and more bruises instead. The woman was suspected of riding the motorcycle at high speed, with her face directly hitting a blunt object. DOI : 10.54052/jhds.v4n1.p25-34